Putting words into practice. (February 2020) - Decise, Donatella; Gheran, Mihaela Palade; Kimhi, Eti; Altmann-Pospischek, Claudia; Spitz, Sabine S.; Casas, Ana; Haidinger, Renate; Calloud de Faudeur, Patricia; Elzayat, Mona; Cardoso, Fatima
Abstract: Many ABC/MBC (advanced or metastatic breast cancer) patients describe feelings of isolation and lack of support [1], often exacerbated by inadequate and insensitive communication. To examine these issues and the changing landscape of the wider breast cancer (BC) community, eight BC patients from across Europe took part in an advisory board. Each patient generously gave up their time to discuss how communication could be enhanced; driven by a desire to improve the experience and bolster support for future ABC/MBC patients. The most powerful and touching message emerged; maintaining the feeling of hope was vitally important as was the knowledge they were not alone in their diagnosis, with patient-to-patient communication representing an important 'lifeline'. It transpired that patients found certain language difficult, confusing and shocking to deal with, particularly as their disease journey was very much an emotional rather than clinical one. For those communicating with ABC/MBC patients, adopting an empathic, patient and personalized language and approach was considered invaluable. Here we examine further the key findings of the advisory board to help shape how, step-by-step, we can change the language we use in practice to effectively and sensitively communicate with ABC/MBC patients. Graphical abstract: Abstract Fig. 1: The Dos and Don'ts of Communicating with ABC/MBC patients, a quick guide. Many HCPs will automatically already follow the tips and avoid the pitfalls outlined below, so this guide is intended only as a reminder. Image 1